Local Ecological Knowledge Informs Nocturnal Mammal Conservation in Ba’Aka Culture in the Central African Republic - Annette S. Gunn; Terence Fuh Neba; K. A. I. Nekaris (Diversity, 2024)
Local ecological knowledge has been shown to convey key information about elusive mammal species. Many of Africa’s nocturnal mammals are not yet considered globally threatened, yet behavioural ecology and population trends across their diverse ranges remain effectively unknown. We conducted semi-structured oral and visual interviews with eight groups of Ba’Aka in three villages (n = 53 males; n = 17 females) using trigger cards, to gain insights into beliefs about nocturnal mammals in the Central African Republic (CAR). We aimed to (1) explore the presence and local knowledge of nocturnal mammals; (2) determine cultural attitudes regarding nocturnal species; and (3) report on Traditional Ecological Knowledge (TEK) in the CAR. Using trigger cards, interviewees identified nine nocturnal mammals. Frequency of key words was measured and presented in word clouds, depicting that angwantibos (Arctocebus aureus) (n = 14), genets (Genetta spp.) (n = 11) and tree hyrax (Dendrohyrax dorsalis) (n = 6) were strongly associated with the supernatural (witchcraft; spiritual protection). The traditional uses of cryptic nocturnal mammals in Ba’Aka culture, including as meat and medicine, may affect the conservation of these species. We suggest a need to protect and include nocturnal mammals with unknown or decreasing populations in wildlife management strategies and community conservation programmes.